The social organization of methamphetamine manufacturing: Roles, identities and persistence. (March 2021) - Copes, Heith; Hochstetler, Andy
Abstract: Purpose: We discuss small batch methamphetamine (i.e., shake meth) cooking as a form of systematic offending using a social organization framework. Method: Semi-structured interviews with 33 people who cooked meth and who were living in faith-based transitional facilities in Alabama. This is coupled with data from an 18-month long ethnography of people who used methamphetamine in rural Alabama that consisted of semi-structured interviews with 52 people and observations and conversations. Results: Internal and external social organization are dependent on the daily concerns of those who use meth, the social context of their lives, and production imperatives. Small batch meth production is a professional crime; it takes some skill, a network, and organizing capacity. It is influenced by the pharmacological properties and symptoms of meth abuse including being cut off from conventional attachments. Conclusions: A defined social organization provides people with roles, expectations, and aspirations. Positions have routines and meanings that embed participants in criminal or drug cultures and contribute to their persistence in crime. Highlights: Social organization of crime allows people to successfully carry out their criminal endeavors. The social organization of small batch meth is structured by police, psychopharmacology of meth, and general patterns of use. Social organizations provides people with roles, expectations, and aspirations, which provide meaning and self-efficacy. The defined roles, agency, and meaning in their lives from having a position in the organization leads to persistence.